Demand side influences on the consumption of alcohol, tobacco and physical activity in Malaysia / Cheah Yong Kang - Cheah, Yong Kang (2014)

(untitled)
In light of alarming evidence of non-communicable diseases and solvable health risk factors, the aim of this study is to examine the relationship between health affecting variables, and demand for alcohol, tobacco and physical activity among adults in Malaysia. Data from the Third National Health and Morbidity Survey (NHMS III) consisting of 30992 respondents and detailed information on individual’s socio-demographic, health and lifestyle profiles is deployed for this purpose. Logit models are applied to examine the factors that influence individuals’ likelihood of consuming alcohol, tobacco and being physically active. The results show that age, income, gender, ethnicity, education, marital status, residing area and employment status are significantly associated with demand for alcohol, tobacco and physical activity. Three main findings can be drawn from this study. Firstly, young individuals, high income earners, males, Chinese, the well-educated, urban dwellers, civil servants, private sector employees, the self-employed and students are more likely to consume alcohol than others. Secondly, young individuals, low income earners, males, Malays, the less-educated, widowed or divorced individuals, rural dwellers, private sector employees and the self-employed are more likely to consume tobacco than others. Thirdly, old individuals, high income earners, females, Indian or others, the well-educated, widowed or divorced individuals, urban dwellers and the unemployed are less likely to participate in physical activity than others. Based on the findings of this study, numerous population-based interventionist measures toward promoting a healthy lifestyle are recommended.